KARAKTERISASI LAJU PERTUMBUHAN MISELIUM JAMUR TIRAM PUTIH (Pleurotus ostreatus) PADA MEDIA DEDAK PADI (Oryza sativaL) DAN JAGUNG (Zea mays L) - Nova Damayanti; Umrah Umrah (Biology Department, Mathematics and natural science, Tadulako University, 2014)
The aim of this study is to characterize the growth rate of mycelium of oyster mushroom (Pleurotus ostreatus). It’s expected that the out come of this study is to find out the best medium which suitable for oyster mushroom propagation. The experiment was designedbased oncompletely randomized design(CRD) consistingof 6 treatmentsand 3 repetitions. The treatment were various ratio of rice bran and corn on the growth medium. The ratio used as treatment (rice : corn) were 100:0 (P1), 80:20 (P2), 60:40 (P3), 40:60 (P4),80:20 (P5), 0:100 (P6). Result of experiment showed that medium P3 was the bestin supporting the growth rate of mycelia which in average of 8,45 mm/day. It were higher than it in other media P4 (7,95 mm/ day), P6 (7,45 mm/ day), P5 (7,08 mm/ day), P1 (6,33 mm/ day) and P2 (5,5 mm/ day). Mycelia on this medium was growth faster that mycelium on the other medium. Keywords: Growthrate,Oyster Mushroom(Pleurotus ostreatus), ricebran (Oryza sativaL), corn (Zea maysL)